Influence of the interaction between two neighboring periodically curved fibers on the stress distribution in a composite material - Kosker, R; Akbarov, SD (CONSULTANTS BUREAU, 2003)
A method is developed for a stress analysis in an infinite elastic body containing two neighboring periodically cophasaly curved fibers located along two parallel lines. The stress distribution is studied when the body is loaded at infinity by uniformly distributed normal forces in the fiber direction. The investigation is carried out within the framework of a piecewise homogeneous body model with the use of exact three-dimensional equations of elasticity theory. Numerical results related to the stress distribution considered and the influence interaction between the fibers on this distribution are given.
Keywords: composite; fibers; stress distribution; fiber curving; 3-DIMENSIONAL THEORY; STABILITY; Mechanics; Materials Science; Polymer Science